Electrical and electronic engineering principles - Morris, Noel M. (Noel Malcolm) 1929- (Longman Scientific & Technical, 1994)
Covers computer software for the solution of circuits and applications in both certificate and diploma courses. The software described includes SPICE (Simulation Program with Integrated Circuits Emphasis), CODAS (Control System Design and Stimulation) and PCS (Process Control Simulation).